Biologie und Epidemiologie der Hormonersatztherapie - Biology and Epidemiology of Hormone Replacement Therapy Diskussionen zur Postmenopausalen Gesundheit - Discussions on Post-Menopausal Health - Lewis, M. A.; Dietel, M.; Scriba, P.; Raff, W.K (Schering Foundation Symposium Proceedings Supplements ;, 2006)
Die Vor- und Nachteile der Hormonersatztherapie (HRT) werden von einer Expertengruppe hinsichtlich der epidemiologischen Beweislage diskutiert. Den Diskussionsschwerpunkt bildet jedoch die Problematik des Brustkrebsrisikos. Unter anderem wird gezeigt, dass die aus epidemiologischen Studien abgeleiteten Ergebnisse sich nicht mit den Wachstumseigenschaften dieser Tumoren decken, so dass weiterführende Bevölkerungsuntersuchungen unter Einbeziehung pathobiologischen Sachverstands notwendig erscheinen. The benefits and risks of hormone replacement therapy (HRT) are discussed by a group of experts with a view towards the evidence provided by recent epidemiological studies. Although all aspects of HRT indications and contra-indications are reviewed, the particular emphasis of this discussion is on breast cancer. Among other things, it is shown that the evidence on breast cancer provided in epidemiological studies does not match the growth characteristics of the tumours, and that further population research incorporating pathobiological assessments is required.